Policy Influence on Chhattisgarh’s Farm System: Shaping Agricultural Practices and Outcomes - Sinha, Sujita (Journal of Advanced Research in Humanities and Social Sciences; Vol 12 No 2 (2025): Journal of Advanced Research in Humanities and Social Sciences, 2025)
Chhattisgarh’s agricultural landscape, characterized by its diverse agro ecological zones and a significant reliance on rain-fed agriculture, is profoundly shaped by a complex interplay of policies at the national and state levels. This abstract examines the multifaceted influence of these policies on the state’s farm system, encompassing aspects such as land tenure, input subsidies, irrigation development, market regulations, credit availability, crop diversification initiatives, and support for sustainable agriculture. It analyzes how these policy interventions impact cropping patterns, technology adoption, farm productivity, income levels of farmers, and the overall sustainability of agricultural practices in Chhattisgarh. The abstract further explores the intended and unintended consequences of these policies, considering their effectiveness in addressing the specific challenges and opportunities within the state’s agricultural sector. It also highlights the role of policy in promoting inclusive agricultural growth, ensuring food security, and mitigating the impacts of climate change on the farm system. Finally, the abstract underscores the need for evidence-based policymaking and adaptive policy frameworks that are responsive to the evolving needs of Chhattisgarh’s farmers and the dynamic agricultural environment.